2011
DOI: 10.3390/rs3020247
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Accuracy of Volunteered Road Map Production in Western Kenya

Abstract: Abstract:The introduction of web based mapping facilities that use satellite imagery, offers local people the possibility to map their environment. However, maps need to be accurate, which is the reason why map making is assigned to professionals. In this paper, we investigated the classification accuracy of road infrastructure from high resolution satellite imagery of an urban area in western Kenya achieved by surveyors and non-surveyors alike, with and without local knowledge. Those with local knowledge clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
0
32
0
1
Order By: Relevance
“…For example, work by Leeuw et al [90] in western Kenya showed that local knowledge plays an important role in improving the accuracy of VGI contributions. In that study, participants with local knowledge, on average, were able to classify roads with over 92% accuracy, compared to professional surveyors (67.7%) and other laymen users without local knowledge of the area (42.9%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, work by Leeuw et al [90] in western Kenya showed that local knowledge plays an important role in improving the accuracy of VGI contributions. In that study, participants with local knowledge, on average, were able to classify roads with over 92% accuracy, compared to professional surveyors (67.7%) and other laymen users without local knowledge of the area (42.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Yet location and local knowledge have been found to be relevant in studies of other types of tasks. A comparison of the contributions of local volunteers in classifying road types from imagery with professional surveyors found that the accuracy increased from 68% to 92% when the data were collected by the local volunteers [33]. OpenStreetMap is built on the idea that local knowledge is of fundamental importance in contributing and tagging features [34] yet many humanitarian mapping exercises use remote mappers to provide rapid information for response teams.…”
Section: Discussionmentioning
confidence: 99%
“…Democratization in map making has the potential "to add to an old science by allowing anyone with access to a computer to upload their findings" (Valdes, 2013). De Leeuw et al (2011) find that the local knowledge that is aggregated via crowdsourcing actually had greater level accuracy than professional surveyors in urban areas of western Kenya. This finding provides support to the power of the crowd and the importance of local knowledge in many map-making endeavors.…”
Section: Crowdmapping Example 1: Google Mapmakermentioning
confidence: 99%